2021
DOI: 10.4103/jcecho.jcecho_118_20
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sacubitril/Valsartan Treatment on Left Ventricular Myocardial Torsion Mechanics in Patients with Heart Failure Reduced Ejection Fraction 2D Speckle Tracking Echocardiography

Abstract: Background: Left ventricular ejection fraction (LVEF) is calculated from volumetric change without representing true myocardial properties. Strain echocardiography has been used to objectively measure myocardial deformation. Myocardial strain can give accurate information about intrinsic myocardial function, and it can be used to detect early-stage cardiovascular diseases, monitor myocardial changes with specific therapies, differentiate cardiomyopathies, and predict the prognosis of several cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…This considerable improvement in the LV myocardial deformation indices raises the possibility that reverse remodeling of the left heart may be a possible mechanism for generating improved cardiac outcomes in the PARADIGM-HF trial [1,34]. This is consistent with recent research which shows that sacubitril/valsartan therapy in HFrEF could induce a chronic and progressive LV unloading state that would relieve myocardial wall tensions and lower LV end-diastolic pressure, leading to cardiac reverse remodeling and restoration of the Frank-Starling mechanism of the LV myocardium, resulting in an increased LVEF [20]. However, although sacubitril/valsartan therapy improved LV systolic function in nonischemic and ischemic HFrEF etiology, the risk of ventricular tachyarrhythmias remains higher in ischemic HFrEF patients compared to nonischemic HFrEF patients [9].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This considerable improvement in the LV myocardial deformation indices raises the possibility that reverse remodeling of the left heart may be a possible mechanism for generating improved cardiac outcomes in the PARADIGM-HF trial [1,34]. This is consistent with recent research which shows that sacubitril/valsartan therapy in HFrEF could induce a chronic and progressive LV unloading state that would relieve myocardial wall tensions and lower LV end-diastolic pressure, leading to cardiac reverse remodeling and restoration of the Frank-Starling mechanism of the LV myocardium, resulting in an increased LVEF [20]. However, although sacubitril/valsartan therapy improved LV systolic function in nonischemic and ischemic HFrEF etiology, the risk of ventricular tachyarrhythmias remains higher in ischemic HFrEF patients compared to nonischemic HFrEF patients [9].…”
Section: Discussionsupporting
confidence: 85%
“…Prior research has demonstrated that sacubitril/valsartan promotes early LV reverse remodeling in chronic HFrEF patients via TTE examination [7,8,34], including GLS, LV twist, and rotation [20]. However, prospective information on radial and circumferential LV deformation following sacubitril/valsartan therapy is lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation